Quatre conceptions de la géographie scolaire : un modèle interprétatif des pratiques d’enseignement de la géographie ? - Jean-François Thémines (Cybergeo)
This paper presents the construction of a model aimed to interpret, from interviews and observations, the various practices of high-school geography teachers. A disciplinary model is composed of four distinct standards of finalities, conceptions of knowledge and geographical space and methods. These four standards allow us to have a better understanding the teacher’s choices towards the contents and learning competences.